1981
DOI: 10.1007/bf00233527
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of neurons projecting to the corpus cardiacum from the larval brain of the tobacco hornworm, Manduca sexta (L.)

Abstract: Retrograde cobalt filling followed by silver intensification revealed new features of the anatomy of neurons which project from the brain to the corpus cardiacum (CC) of the fifth instar larva of Manduca sexta. Filling via the fused nervi corporis cardiaci (NCC) I + II demonstrated four groups of cell bodies (Ia, Ib, II, and III) previously described by Nijhout (1975), plus three major axonal tracts (A, B, and C), and four previously unobserved areas of dendritic branching, dendritic fields (DF) 1, 2, 3, and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The classification of brain neurosecretory cells used in the present study follows that used by Buys and Gibbs (1981), Copenhaver and Truman (1986), Homberg et al (1991), and Žitňan et al (1995). The results of our immunostaining were comparable to those of previous studies (Homberg et al, 1991, and Davis et al, 1997 [SCP B ]; Veenstra and Hagedorn, 1991, and Chen et al, 1994 [DH]; Westbrook et al, 1993, and Dai et al, 1994 [PTTH]; Davis et al 1997 [AS]; Wise et al, 2002 [CZ]).…”
Section: Resultsmentioning
confidence: 99%
“…The classification of brain neurosecretory cells used in the present study follows that used by Buys and Gibbs (1981), Copenhaver and Truman (1986), Homberg et al (1991), and Žitňan et al (1995). The results of our immunostaining were comparable to those of previous studies (Homberg et al, 1991, and Davis et al, 1997 [SCP B ]; Veenstra and Hagedorn, 1991, and Chen et al, 1994 [DH]; Westbrook et al, 1993, and Dai et al, 1994 [PTTH]; Davis et al 1997 [AS]; Wise et al, 2002 [CZ]).…”
Section: Resultsmentioning
confidence: 99%
“…These cells occur in a cluster known as the IIa group (terminology of Buys and Gibbs, 1981, as elaborated by Copenhaver and Truman, 1986;Homberg et al, 1991;Ž itň an et al, 1995). On the basis of their numbers, relative sizes, and immunoreactivities, five different subtypes of neuroendocrine cells are recognized in group IIa (Ž itň an et al, 1995).…”
Section: Immunocytochemistrymentioning
confidence: 98%
“…In Manduca larvae 4 groups of cells (Fig. 15.3) were identified, cells of groups la, lb, and II located in the median or paramedian region of the protocerebrum and group III in the dorsolateral cortex (Nijhout, 1975 a; Buys & Gibbs, 1981;Carrow et al, 1984;Copenhaver &Truman, 1986). The large cells of group II stain with .4), the smaller cells stain lightly (Bhaskaran & Jones, 1980).…”
mentioning
confidence: 96%
“…The large cells of group II stain with .4), the smaller cells stain lightly (Bhaskaran & Jones, 1980). The axons of group la and lb course through the brain on the same side and join with the axon tracts from contralateral cells of groups II and III to form NCC I + II before exiting from the brain (Copenhaver & Truman, 1986: Buys & Gibbs, 1981). Filling of NCC I + II toward the CC-CA showed that many of the axons terminated in the CA, branching all over the glands.…”
mentioning
confidence: 96%